2022
DOI: 10.1021/acs.jafc.2c03997
|View full text |Cite
|
Sign up to set email alerts
|

Discovery of Azo-Aminopyrimidines as Novel and Potent Chitinase OfChi-h Inhibitors via Structure-Based Virtual Screening and Rational Lead Optimization

Abstract: Chitinase OfChi-h, from the destructive agricultural pest Ostrinia furnacalis, is considered as a promising target for green pest control and management. In this study, structure-based virtual screening and rational molecular optimization led to the synthesis of a series of azo-aminopyrimidine derivatives as a novel class of OfChi-h inhibitors. Among them, the most potent compound 8f, with a benzyl on the amino group at the 4-position of pyrimidine, exhibited a K i value of 64.7 nM against OfChi-h. In addition… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
16
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 13 publications
(16 citation statements)
references
References 28 publications
0
16
0
Order By: Relevance
“…A series of azoaminopyrimidine derivatives was designed and synthesized as a novel class of Of Chi-h inhibitors via virtual screening and rational molecular optimization. 36 The most potent compound 2a, with benzyl on the amino group at the 4 position of pyrimidine, displayed a K i value of 0.0647 μM toward Of Chi-h (Figure 4 and Table 1).…”
Section: ■ Inhibitors Of Chi-hmentioning
confidence: 99%
“…A series of azoaminopyrimidine derivatives was designed and synthesized as a novel class of Of Chi-h inhibitors via virtual screening and rational molecular optimization. 36 The most potent compound 2a, with benzyl on the amino group at the 4 position of pyrimidine, displayed a K i value of 0.0647 μM toward Of Chi-h (Figure 4 and Table 1).…”
Section: ■ Inhibitors Of Chi-hmentioning
confidence: 99%
“…Recently, some small-molecule Chitinase inhibitors with planar structures, such as phlegmacin B 1 , azo-aminopyrimidines, and dipyrido-pyrimidine derivatives, have been reported (Figure A). The binding modes revealed that these potent Chitinase inhibitors located at the reducing end (+1 and +2 subsites) and formed π–π stacking interactions with aromatic tryptophan residues. The Chitinase inhibitory mechanism indicates that an aromatic plane is more suitable for the substrate binding groove of Chitinase .…”
Section: Introductionmentioning
confidence: 99%
“…These crystallographic studies of Of Chi-h lay a solid foundation for the design and discovery of structure-based novel inhibitors. 10 In view of the importance of Of Chi-h, several inhibitors with different chemical structures have been reported to date, such as chitoheptaose, 10 TMG-(GlcNAc) 4 , 10,12 phlegmacin B 1 , 13 dipyrido-pyrimidines, 14,15 azo-aminopyrimidines, 16 berberines, 17 rhodanines, 18 methylcarbamoyl-guanidines, 19,20 thiazolylhydrazones, 21 deoxyshikonin, 22 polonimides, 23 lynamicin B, 24 and SN-38 25 (Figure 1). However, many of the reported inhibitors (especially glycosyl-based inhibitors) have limita-tions in poor physicochemical properties and complicated synthesis processes.…”
Section: Introductionmentioning
confidence: 99%
“…However, many of the reported inhibitors (especially glycosyl-based inhibitors) have limita-tions in poor physicochemical properties and complicated synthesis processes. 16,17 Thus, the focus of the present study is to develop a type of novel and potent Of Chi-h inhibitor with a concise structure and suitable pesticide-like properties.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation